2015
DOI: 10.5603/cj.a2015.0059
|View full text |Cite
|
Sign up to set email alerts
|

Standard 12-lead electrocardiogram tele-transmission: Support in diagnosing cardiovascular diseases in operations undertaken by Warsaw-area basic medical rescue teams between 2009 and 2013

Abstract: (Cardiol J 2015; 22, 6: 675-682)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…5 Tele-ECG has been used very effectively to improve the ACS detection rate by the basic medial rescue team, even without a physician. 6 Researchers in India have also tried to find a solution in the form of a portable handheld electrocardiography (ECG) machine. 7 These machines, however, require additional cost, training and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…5 Tele-ECG has been used very effectively to improve the ACS detection rate by the basic medial rescue team, even without a physician. 6 Researchers in India have also tried to find a solution in the form of a portable handheld electrocardiography (ECG) machine. 7 These machines, however, require additional cost, training and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…The indications for remote ECG monitoring in the diagnostic workup of cardiac patients are directly related to the benefits of this technique over standard ECG monitoring (TABLE 3). 18,[22][23][24][25][26][27][28][29][30][31][32][33][34] We would like to emphasize that in the case of frequent symptoms (occurring daily or several times a week), conventional ambulatory ECG monitoring (Holter), which in practice can be used for continuous monitoring for up to 72 hours, should be the diagnostic method of choice. 34 In the case of indications for an ECG assessment over a period longer than 14 days, the preferred diagnostic method should be remote ECG monitoring.…”
Section: Indications For Remote Electrocardiographic Monitoringmentioning
confidence: 99%
“…13,22 Transmission of short event -based ECG recordings by medical personnel is a typical part of teleconsultation, which may be also used in emergency medical services and as part of cooperation between higher -level specialist facilities and both primary care and lower -level referral facilities. 16,23 The transfer of continuous ECG recording with the option of online analysis is an advanced method that makes it possible to analyze the complete uninterrupted ECG recording. Such a recording may be sent online to a monitoring center in real time or at a later time.…”
Section: Indications For Remote Electrocardiographic Monitoringmentioning
confidence: 99%
“…24,25 Kleinrok et al 26 showed that 1500 of 7000 patients in whom ECG transmission was applied were diagnosed with STEMI. Rekosz et al 27 analyzed MET interventions in the region of Warsaw in the years 2009 to 2013 and showed that ECG transmission considerably improved the diagnostic ability of METs, which led to better treatment of patients with CVDs. Transmitting electrocardiograms from an ambulance to an invasive cardiology center is one of the strategies used by METs for the management of patients with STEMI.…”
Section: What's New?mentioning
confidence: 99%